The Influence of Online Customer Review, Online Customer Rating, Marketing Content on Fashion Buying Interest in Tiktokshop - Fitriani, Desvita; Kusumaningtyas, Dian (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research aim : The purpose of this study is to find out the Influence of Online Customer Review, Online Customer Rating, and Marketing Content on Fashion Buying Interest in Tiktokshop Design/Methode/Approach : The research uses a Causal Qualitative approach with a case study on consumers who have made fashion purchases at Tiktokshop. The data collection method is carried out through the distribution of questionnaires or questionnaires. The sample taken is as many as 40 people who will later be tested for validity and reliability using multiple linear regression analysis and hypothesis tests (t and f tests). Research Finding : In this study, the results of the variables T Test and F Test Online Customer Review (X1) and Online Customer Rating (X2) did not have a significant effect on Buying Interest (Y). Meanwhile, the Content Marketing (X3) variable has a significant effect. In addition, it was 69.2%. So, it can be interpreted that there are still variations of other factors that were not studied in this study, namely 30.8%. Theoretical contribution/Originality : This study provides a significant theoretical contribution and strengthens the literature on the findings of the influence of independent variables on dependent variables Practitionel/Policy implication : In practice, this study provides a solution to identify what causes affect buying interest Research limitation : The variable currently used does not have an influence on buying interest of 69.2% so there are still several variations of other variables that are not studied in this study, namely 30.8% so further research is needed